PENGGUNAAN MOBILE BANKING SEBAGAI UPAYA MEMPERLANCAR TRANSAKSI ELEKTRONIK NASABAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK - Evi Okli Lailani; Tannia Regina (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
Service quality in banking is very important considering it can affect customer satisfaction and loyalty. Many strategies are used by the bank for service quality, including the dimensions of security service quality related to guaranteeing the confidentiality of customer data, the absence of data manipulation, security using Mobile Banking services, the dimensions of speed of Mobile Banking services related to the provider operator network and quality of network maintenance, dimensions of accuracy related to the suitability of information received by customers, clarity of information received, dimensions of trust related to customer trust in using services, banks gain loyalty from customers for Mobile Banking products, and dimensions of education related to the educational process between the two sides of employees and customers regarding the explanation of information about Mobile Banking service products. The quality of BRI Mobile Banking services through the dimensions of security, speed, accuracy, and trust and education has an important role in customer loyalty in using service products from BRI. in fact in the field of security and education to customers is an important priority in the development of Mobile Banking services. customers need a sense of security when using Mobile Banking transactions and customers need education from BRI as they experience difficulties when operating. BRI makes efforts to protect customers when conducting online transactions. Strategy is centered on security and education. Security and education are considered quite important because the gate makes customers feel safe and gets rewards from the education system. This element can encourage other elements in meeting the needs of BRI customers.